The Story of CO2 : Big Ideas for a Small Molecule - Ozin, Geoffrey; Ghoussoub, Mireille (University of Toronto Press, 2020)
The climate crisis requires that we drastically reduce carbon dioxide emissions across all sectors of society. The Story of CO2 contributes to this vital conversation by highlighting the cutting-edge science and emerging technologies - a number of which are already commercially available - that can transform carbon dioxide into a myriad of products such as feedstock chemicals, polymers, pharmaceuticals, and fuels. This approach allows us to reconsider CO2 as a resource, and to add "carbon capture and use" to our other tools in the fight against catastrophic climate change. The Story of CO2 explores all aspects of carbon dioxide, from the atomic to the universal perspective, and takes the reader on an epic journey into our physical world, starting from the moment of the Big Bang, all the way to the present world in which atmospheric CO2 concentrations continue to grow. This story seeks to inspire readers with the latest carbon utilization technologies and explain how they fit within the broader context of carbon mitigation strategies in the shift towards a sustainable energy economy.